Potential Lethal Co-infections in COVID-19: A Study Based on Literature Review - Sah , Shiv Nandan; Ghimire, Arjun; Sah, Ranjit Kumar; Sah, Pradeep Kumar; Caplash, Neena; Sharma, Prince (Nepal Journal of Science and Technology, 2021)
Co-infection with other respiratory pathogens has been reported in patients with COVID-19. Common respiratory pathogens can infect as co-pathogens during SARS-nCoV-2 infections. The aim of this article is to spread knowledge regarding possible co-infections during COVID-19, and reduce their occurrence. Google scholar was used to search the literature for possible co-infections in the people with COVID-19 and reviewed the existing published data. In most cases, co-infections are common due to Streptococcus pneumoniae, Staphylococcus aureus, Klebsiella pneumoniae, Mycoplasma pneumoniae, Chlamydia pneumonia, Legionella pneumophila, and Acinetobacter baumannii.Prevalence of fungal and viral co-infections is low. However, Candida species and Aspergillus flavusare the common co-infective fungi. Viruses such as Influenza, Corona virus, Rhinovirus/ Enterovirus, Parainfluenza, Metapneumo virus, Influenza B virus, and Human immunodeficiency virus have also been reported as co-infecting agents during COVID-19. Influenza A was one of the most common co-infective viruses, which may have caused initial false-negative results of a real-time RT-PCR for severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). The prevalence of co-infections could be up to 50% among non-survivors. Only newly developed syndromic multiplex panels that incorporate SARS-CoV-2 may facilitate the early detection of co-infections. The suitable antimicrobial agents can be recommended for the co-infections caused by other respiratory pathogens during COVID-19.